Maternal insulin resistance, triglycerides and cord blood insulin in relation to post‐natal weight trajectories and body composition in the offspring up to 2 years. Issue 12 (11th September 2013) - Brunner, S.; Schmid, D.; Hüttinger, K.; Much, D.; Heimberg, E.; Sedlmeier, E.‐M.; Brüderl, M.; Kratzsch, J.; Bader, B. L.; Amann‐Gassner, U.; Hauner, H.
Abstract Aims The intrauterine metabolic environment might have a programming effect on offspring body composition. We aimed to explore associations of maternal variables of glucose and lipid metabolism during pregnancy, as well as cord blood insulin, with infant growth and body composition up to 2 years post‐partum. Methods Data of pregnant women and their infants came from a randomized controlled trial designed to investigate the impact of nutritional fatty acids on adipose tissue development in the offspring. Of the 208 pregnant women enrolled, 118 infants were examined at 2 years. In the present analysis, maternal fasting plasma insulin, homeostasis model assessment of insulin resistance and serum triglycerides measured during pregnancy, as well as insulin in umbilical cord plasma, were related to infant growth and body composition assessed by skinfold thickness measurements and abdominal ultrasonography up to 2 years of age. Results Maternal homeostasis model assessment of insulin resistance at the 32nd week of gestation was significantly inversely associated with infant lean body mass at birth, whereas the change in serum triglycerides during pregnancy was positively associated with ponderal index at 4 months, but not at later time points. Cord plasma insulin correlated positively with birthweight and neonatal fat mass and was inversely associated with body weight gain up to 2 years after multiple adjustments. Subsequent stratification by gender revealed that this relationship with weight gain was stronger, and significant only in girls. Conclusions Cord blood insulin is inversely associated with subsequent infant weight gain up to 2 years and this seems to be more pronounced in girls.